2022
DOI: 10.3233/wor-205239
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of working conditions and occupational health in home office

Abstract: BACKGROUND: In times of the COVID-19 pandemic, employees around the world may be practicing part-time telework at home. Little is known about the working conditions at home and its impact on the employee’s occupational health. OBJECTIVE: This systematic review examines the working conditions at employees’ homes, the work-related disorders associated with working from home, organizations’ perceptions of ergonomics at home and how they support their teleworkers. METHODS: A search of electronic databases (Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
1
35
0
2
Order By: Relevance
“…We also observed that physical HRQOL decreased with more time passed since the implementation of pandemic measures in Switzerland. Discontinuation of commuting to the office and thus increased sedentary behaviour over time could be one reason [ 57 ], but also the lack of ergonomic work environments at home might have caused health issues such as back pain [ 58 60 ]. We found that individuals who were in isolation at time of the survey or who have already had COVID-19 were at risk for low physical HRQOL, likely because staying at home and the impact being/having been sick with COVID-19 prevented them from physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that physical HRQOL decreased with more time passed since the implementation of pandemic measures in Switzerland. Discontinuation of commuting to the office and thus increased sedentary behaviour over time could be one reason [ 57 ], but also the lack of ergonomic work environments at home might have caused health issues such as back pain [ 58 60 ]. We found that individuals who were in isolation at time of the survey or who have already had COVID-19 were at risk for low physical HRQOL, likely because staying at home and the impact being/having been sick with COVID-19 prevented them from physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…It can, therefore, be seen that it is precisely the second territory to which the home office can be assigned those harbors certain potential for conflict regarding the perceived privacy in home office. Vieira and Meirinhos ( 2021 ) and Wütschert et al ( 2021 ) studies provided additional evidence that perceived privacy among home-based teleworkers may play a supporting role in mental health. The construct of perceived privacy is associated with disturbance and distraction and represents the perceived control of outside stimuli regarding to visual privacy and acoustic privacy (Wohlers and Hertel 2017 ; Elsbach and Pratt 2007 ; Haapakangas et al 2018a , b ).…”
Section: Introductionmentioning
confidence: 96%
“…Studies have previously pointed out the lack of organizational support for teleworkers when it comes to providing ergonomic equipment as well as support and guidance in installation and usage (35). Research suggests that besides providing ergonomic furniture and equipment, education on how to properly set up workstations may be of as much importance.…”
Section: Discussionmentioning
confidence: 99%